Tropical easterly waves over Costa Rica and their relationship to the diurnal cycle of rainfall - Wiggins, Rani M. (2023)
Using an index of tropical easterly wave (TEW) activity derived from spacetime-filtered outgoing longwave radiation, we construct composites of long-term hourly surface meteorological observations and morningtime sounding data collected near San José, Costa Rica to investigate how TEWs affect the diurnal cycle of rainfall over land. Our results indicate that TEWs enhance the frequency of occurrence of rain during convectively active conditions over the course of the diurnal cycle. By contrast, rainfall conditional intensity sensitivity to TEW phase appears more nuanced, with indications that active conditions induce a slight delay in the timing of the diurnal peak intensity but a longer duration of heavier rainfall. Analysis of associated hourly surface meteorology along with sounding profiles and derived thermodynamic parameters points to both initial vertical and time-evolving surface conditions regulating diurnal behavior, such as greater instability and higher precipitable water in morningtime profiles under active phase conditions.